Role of localized graphitization on the electrical and magnetic properties of activated carbon - Raj, Kovummal Govind; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2017)
The correlation between the magnetic and electrical properties of activated carbon with its microstructure is studied. The changes in the microstructure of activated carbon, after activation at three different temperatures (800 degrees C, 900 degrees C, 1000 degrees C) using different amounts of the activating agent, KOH (KOH/C ratio of 1: 1, 2: 1, 3: 1 and 4: 1), are studied using X-ray diffraction and Raman spectroscopy. The results showed the formation of localized nanographitic domains, along with the changes in the surface area and porosity of the activated carbon. The changes in the microstructure are found to be directly correlated with the magnetic properties and electrical conductivity. The interplay between ordering and disordering parameters in the activated carbon is found to determine the electrical conductivity and magnetic properties.